Development of a test plan and a testbed for performance analysis of MEMS-based IMUs under vibration conditions. (1st July 2020) - Capriglione, D.; Carratù, M.; Catelani, M.; Ciani, L.; Patrizi, G.; Singuaroli, R.; Pietrosanto, A.; Sommella, P.
Highlights: Characterization of Micro‐Electro‐Mechanical Systems (MEMS). Reliability and metrological performance analyses in real scenarios of IMUs. Development of a test plan and a testbed for the IMUs performance analysis. Random vibration tests and sweep sine vibration tests for automotive applications. Abstract: Micro-Electro-Mechanical Systems (MEMS) are today widespread in many industrial and consumer applications. In the field of terrestrial transportation, cellular, wearable devices, robotics, drone, to cite a few, MEMS-based Inertial Measurement Units (IMUs) are widely employed for assuring several tasks as for the object tracking, self-driving vehicles, human motion and so on. Expected performance of such systems and also recent literature and technical standards miss considering both a context-awareness reliability analysis and metrological performance analyses of MEMS-based IMUs when operating in real scenarios characterized by the presence of significant temperature excursions, humidity, vibrations, mechanical shocks and so on. In particular, standard procedures to be applied for testing MEMS-based IMUs are not still available. Trying to fill these needs, this paper proposes both a suitable testbed and test plans for performance analysis of such kinds of devices under vibration conditions. The application to a real IMUs has confirmed that the proposed tests allow identifying the effects of mechanical stress on both the reliability and metrological performance of such devices. These results could be useful also for the international committees involved in the definition of technical standards to be adopted for testing these kinds of devices.